Turkey : Seventh Review Under the Stand-By Arrangement, and Requests for Waiver of Applicability and Nonobservance of Performance Criteria, Rephasing of Purchases, and Extension of Arrangement-Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Turkey's Seventh Review Under the Stand-By Arrangement, and Requests for Waiver of Applicability and Nonobservance of Performance Criteria. Successful macroeconomic management delivered an impressive economic performance in 2003. However, budget slippages interrupted this success, delaying the completion of the Seventh Review. The challenge in the final year of the program is to maintain macroeconomic policies firmly on track and to move decisively on a comprehensive program of structural reforms to safeguard and advance the recent achievements.